Memahami inner child dalam mengatasi luka masa kecil - Karim, Nusaiba Nisa’ul (Maliki Interdisciplinary Journal, 2024)
The inner child in a person is illustrated as the childish traits and behavior that exist within a person. Because it is formed from different experiences and circumstances when they were young, the condition of each person’s inner child is not the same. Good experiences and bad experiences in the past always have an impact on a person’s life when they are adults. The experiences that children have when they are small are also related to the parenting style of their parents. It is very possible that acts of violence occur against children so that the child’s relationship with his parents is not well established and the child tends to become a quiet person. So it is not surprising that the injured inner child will continue to be carried over into adulthood and even become a parent. If a wounded inner child is continuously ignored, it will disrupt a person’s life, especially their mental condition. Therefore, understanding is needed in healing these inner wounds. In preparing this journal, the author obtained data through literature review. Through a literature review, the author looks for data related to the inner child and attempts to overcome it through notes, books, articles, etc. related to the discussion. The result of writing this journal was an effort to heal childhood emotional wounds, namely by writing, opening up, and carrying out ho’oponopono therapy independently.